2017
DOI: 10.21776/ub.jam2017.015.04.14
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Effect Between Compensation, Leadership and Organizational Culture on Employee Performance Improvement

Abstract: Abstract:The performance of employees is closely related to compensation (total cash), organizational culture, and leadership. This research aims to identify the independent variables: compensation (X1), leadership (X2), and organizational culture (X3) by dependent variable of performance (Y). The result of multiple regression analysis had identified that organizational culture dominantly influenced the employee performance in the Integrated Office of Malang City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…When organizational culture can support participation, it will result in job satisfaction which encourages employees to be more creative in improving their performance (Erniwati et al, 2020). Fithriana and Adi (2017) discovered that organizational culture has the most dominant influence on employee performance in the Malang City Government. Lolowang et al (2019) found a positive and significant influence of organizational culture applied to employee performance at the Jayapura Village Office.…”
Section: Organizational Culturementioning
confidence: 99%
See 1 more Smart Citation
“…When organizational culture can support participation, it will result in job satisfaction which encourages employees to be more creative in improving their performance (Erniwati et al, 2020). Fithriana and Adi (2017) discovered that organizational culture has the most dominant influence on employee performance in the Malang City Government. Lolowang et al (2019) found a positive and significant influence of organizational culture applied to employee performance at the Jayapura Village Office.…”
Section: Organizational Culturementioning
confidence: 99%
“…Meanwhile, research by Ogbonna and Harris (2000) and Wibowo and Saputra (2017) found that leadership style did not have a significant effect on employee performance. Moreover, Fithriana and Adi (2017) and Lolowang et al (2019) found a positive influence of organizational culture on employee performance, while Syauta et al (2012) discovered the opposite, organizational culture does not have a significant influence on employee performance. Furthermore, Siengthai and Pila-Ngarm (2016) and Hendri (2019) revealed that job satisfaction had a significant positive effect on employee performance, while Crossman and Abou-Zaki (2003) found job satisfaction did not affect employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…This further research strengthened by the research conducted by Taurisa and Ratnawati [11], Afnita et.al [9], Abadiyah and Purwanto [18], Fauzi et.al [13] which shows that there is a strong influence between organizational culture on employee performance. According to Fitriana and Adi [19] the dominant factor influencing perfomance is organizational culture. Based on research, it can be seen that strenght or weak organizational culture on BNI branch Perguruan Tinggi Bandung is influnced by indicators innovative attitudes, risk taking, rigorous service, attention into works details, providing of the best results, helping colleagues when problems occur, helping supervisor, teamwork, solidarity, competing in achieving work excellence, actively competitive in work, dedication to providing the best, and mainting organizational stability.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%